Social communication from the perspective of religious and scientific moderation: Building harmonious dialogue in the digital era - Irwanto, Irwanto (Priviet Social Sciences Journal, 2025)
Social communication has changed entirely because of the advancement of digital technology, especially in the context of religious life. With an emphasis on initiatives to foster peaceful discourse in the digital age, this study explores social communication from the perspectives of religious moderation and science. Using a literature review approach, this study examined scholarly works, research reports, and current scientific sources on social communication tactics, digital literacy, and religious moderation. The results show that religiously moderated communication can be a useful tool for reducing polarization, lowering the risk of online extremism, and promoting tolerance and respect for diversity. From a scientific standpoint, digital literacy plays a vital role in strengthening the public's critical ability toward the flow of information, allowing them to filter extremist propaganda, hate speech, and hoaxes. Additionally, communication tactics that combine scientific methods with religious principles can make messages more inclusive and logical, while also enhancing their validity. To create a healthy, moderate, and long-lasting social communication ecosystem, this study also highlights the significance of multi-stakeholder collaboration among religious leaders, academics, educators, digital media managers, and the government. Therefore, this study claims that integrating scientific and religious moderation is essential for fostering peaceful socio-religious discourse in the digital age.